Root Assessment Method (RAM): A novel multi-criteria decision making method and its applications in sustainability challenges - Sotoudeh-Anvari, Alireza (Journal of cleaner production, 2023)
The major objective of this paper is to introduce a novel multi-criteria decision making method (MCDM) called Root Assessment Method (RAM) which is easy to understand, straightforward to use and comparable with other well-known MCDM methods. RAM is motivated by the shortcomings of existing MCDM methods to obtain a reliable result in a decision problem and also the fact that decision maker (DM) should understand the whole decision making process to be able to avoid possible computational pitfalls. To do so, we define an aggregating function to rank the alternatives based on a radical expression which its radicand and index are the sums of benefit and cost criteria of each alternative, respectively. Accordingly, RAM allows a different compensation degree between beneficial and non-beneficial criteria which is rare in existing MCDM methods. As the advantages of RAM, the ranking result is not influenced by additional parameter, beneficial and non-beneficial criteria can be simultaneously considered without any transformation and pairwise comparisons are not used. On the other hand, it is observed that RAM can provide the advantage of preventing rank reversal in two case studies, whereas TOPSIS and VIKOR are subject to this problem in the same cases. As another contribution, a new heuristic procedure is suggested to compare the ranking results obtained by RAM with other methods. Ten numerical examples demonstrate that RAM results are consistent with its presumed function and are easily interpretable for a DM who may not be well acquainted with theoretical aspects of MCDM methods. Examples are positioned in the field of sustainability research as the area with wide application of MCDM methods. The results provided by RAM are encouraging and we hope this method contributes to enrich decision theory.